2001
DOI: 10.1038/sj.onc.1204594
|View full text |Cite
|
Sign up to set email alerts
|

Translocations involving anaplastic lymphoma kinase (ALK)

Abstract: Anaplastic large-cell lymphoma (ALCL) comprises a group of non-Hodgkin's lymphomas (NHLs) that were ®rst described in 1985 by Stein and co-workers and are characterized by the expression of the CD30/Ki-1 antigen (Stein et al., 1985). Approximately half of these lymphomas are associated with a typical chromosomal translocation, t(2;5)(p23;q35). Much confusion about the exact classi®cation and clinicopathological features of this subgroup of NHL was clari®ed with the identi®ca-tion of NPM ± ALK (nucleophosmin-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
204
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(211 citation statements)
references
References 122 publications
(116 reference statements)
2
204
2
3
Order By: Relevance
“…pp60 c-src is not a physical intermediate of Vav3 and NPM-ALK association since mutation of its binding site (Y418F) had no effect on the association. Interestingly, assessment of the intrinsic tyrosine kinase activity of NPM-ALK with the anti-pNPM-ALK(Y664) antibody confirmed that three of the mutants, namely, Y338F, Y342F and Y343F, had reduced kinase activity (Duyster et al, 2001).The fact that two of them are still capable of binding Vav3 indicates that Y343 is probably phosphorylated by another kinase still to identify.…”
Section: Role Of Gtpases In Npm-alk( þ ) Alclsmentioning
confidence: 98%
See 2 more Smart Citations
“…pp60 c-src is not a physical intermediate of Vav3 and NPM-ALK association since mutation of its binding site (Y418F) had no effect on the association. Interestingly, assessment of the intrinsic tyrosine kinase activity of NPM-ALK with the anti-pNPM-ALK(Y664) antibody confirmed that three of the mutants, namely, Y338F, Y342F and Y343F, had reduced kinase activity (Duyster et al, 2001).The fact that two of them are still capable of binding Vav3 indicates that Y343 is probably phosphorylated by another kinase still to identify.…”
Section: Role Of Gtpases In Npm-alk( þ ) Alclsmentioning
confidence: 98%
“…Cells were lysed 48 h post nucleofection. pcDNA3 containing wild-type NPM-ALK or the Y338F, Y342F, Y343F, Y418F and Y664F mutants were already described (Duyster et al, 2001;Cussac et al, 2004). pcDNA3-EGFP-Rac1T17N was a generous gift from Dr K Hahn (University of North Carolina, Chapel Hill, NC, USA).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Previous in vitro studies have demonstrated that NPM-ALK is capable of activating the phosphatidylinositol 3-kinase (PI3K)-Akt/PKB pathway. 15,16 Activation of this pathway results in phosphorylation of the BCL-2 family protein BAD, preventing BAD from binding to the antiapoptotic proteins BCL-2 and BCL-XL and inhibiting their function.…”
mentioning
confidence: 99%
“…Cytogenetically, the 2p23 locus is translocated frequently with 5q35, and less frequently with 1p25, 3q21 or 2q35. (34) In 1994, Morris et al showed that the t(2;5) translocation fused the NPM1 gene on 5q35 to a previously unidentified protein tyrosine kinase gene, ALK, on 2p23. (35) In the NPM-ALK chimeric kinase, the N-terminus of NPM (amino acids 1-117) is fused to the catalytic domain of ALK (amino acids 1058-1620).…”
Section: Npm-alk Chimeric Kinase In Alclmentioning
confidence: 99%